The Influence of Liquidity Management and Specific Banking Factors on Profitability Through Credit Growth in Indonesia - Darma, Kurnia; Mulyantini, Sri; Jubaedah, Jubaedah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to determine the influence of Liquidity Management and Specific Banking Factors on Profitability through Credit Growth. The population of this research is 17 commercial banks listed on the Indonesia Stock Exchange. The method used in this research is purposive sampling, 6 periods from 2018 – 2023, 10 banking companies on IDX, a total of 60 observations. Data analysis uses the panel data regression method processed using Eviews version 13. The results of this research are: (1) Liquidity, Capital Adequacy, Investment Policy, and Credit Growth have no effect on Profitability, (2) Problematic Credit and Banking Efficiency have an effect on profitability, (3) Liquidity and Investment Policy influence on credit growth, (4) Capital adequacy, problem loans, and banking efficiency have no effect on credit growth, (5) Liquidity, capital adequacy, problem loans, Investment Policy, and banking efficiency has no effect on profitability through credit growth.